Influence of Acrylated Lactide‐Caprolactone Macromonomers on the Performance of High Biomass Content Pressure‐Sensitive Adhesives. Issue 10 (1st October 2013) - Pu, Gang; Hauge, Drew A.; Gu, Cheng; Zhang, Jilin; Severtson, Steven J.; Wang, Wenjun; Houtman, Carl J.; Izadi, Hadi; Penlidis, Alexander
Abstract Results from a study of the influence of macromonomer (MM) composition on the properties of high‐biomass content adhesive polymers are reported. Pressure‐sensitive adhesives (PSAs) are synthesized through miniemulsion polymerization of n‐butyl acrylate, vinyl acetate, and methacrylic acid with lactide‐containing MMs. The MMs are generated from bulk ring‐opening polymerizations of lactide and ϵ‐caprolactone with 2‐hydroxyethyl methacrylate. Both meso‐lactide and L‐lactide were used to produce MMs of various chain lengths and compositions. It was found that properties of generated polymers show a strong dependency both on the content and type of lactide utilized. Standard adhesive tests run on the PSAs demonstrate that MM composition can be used to provide significant control over perfromance properties.<inline-graphic xlink:href="ark:/27927/pgg3ss0642b" content-type="mren201300160-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />